Processing range data for autonomous vehicle navigation - Wijaya, Andrew. (2010)
This project is basically to continue the research that has been done by last year FYP students. The idea of this project is to investigate the possibilities of a driverless vehicle, in this case is Segbot (Robotic version of the Segway RMP). Segbot is a two-wheeled robot, using the same principle of segway to balance itself. By connected to rangefinder sensor, Segbot is supposed to map surrounding area, do path planning and obstacle avoidance.